(untitled) (The Research of Medical Science Review, 2025)
Objective: The research determines the bacterial species most commonly found in burn wounds along with their antibiotic susceptibility patterns at a tertiary care center in Pakistan with analysis on treatment strategies and resistance management implications. Study Design: Cross-sectional descriptive study. Place and Duration of Study: Department of Microbiology, PNS SHIFA Hospital, Karachi, Pakistan, conducted between August 2024 and January Methodology: Medical staff obtained bacterial cultures from wound swabs of patients who received hospital admission because of burn injuries. The research team collected information about patient characteristics together with details about the kind of burns and bacterial test results. Standard microbiological methods determined antibiotic susceptibility while the research analysis occurred through SPSS Version 25 with a p-value < 0.05 significance level. Results: Of all pathogenic microbes analyzed in the study Staphylococcus aureus was the most common with Methicillin-Resistant Staphylococcus aureus (MRSA) types identified in 85.7 percent of the cases. The analysis showed high antibiotic resistance rates for penicillin (100%) together with doxycycline (95%) and erythromycin (90%). However, Staphylococcus aureus showed high effectiveness against vancomycin and linezolid (95%). Conclusion: The study is expected to demonstrate the distribution of bacterial infections in burn wounds and their antibiotic resistance, providing critical insights into the effective management of these infections in the Pakistani setting. The findings will support the development of tailored antibiotic therapies to combat resistance and improve patient outcomes.